Unblocking High-Value Botanical Value Chains: Is There a Role for Blockchain Systems? - Heinrich, Michael; Scotti, Francesca; Booker, Anthony; Fitzgerald, Martin; Kum, Ka Yui; Löbel, Katja (Frontiers in Pharmacology, 2019)
Blockchain systems are a fast emerging and a currently widely discussed novel strategy for a decentralised cryptographically-enhanced digital ledger recording transactions among stakeholders. This perspective paper looks at its potential uses in the context of high value and mostly low volume botanical material traded globally and used as medicines, health foods, in cosmetics and other applications. We offer a perspective on key areas in the supply of such products globally and how blockchain systems may help in sustainable sourcing, quality assurance, and in tackling supply problems in cases of complex multiherbal preparations. Both open and closed blockchain systems are feasible, and it seems likely that, at least in the initial development, closed ones are the main ones to be utilized. While blockchain’s potential is not yet clear, the examples presented here highlight the opportunities of this new technology.